Participare și libertate politică - Czobor, Mihaela (Calitatea Vieții, 1991)
Being fundamental in a society which wants to be considerate as a democratic one, the political participation becomes possible at the confluence between the political area (the area of individual liberties) and the individual experiences in front of the political reality and the political personality of men, being conditioned by different political styles. Either as participation or non-participation, these two possibilities involve the reference to liberty, both as a condition or a result of them. Leading to self-determination, to power, to the ability of bringing something new in the social and political reality, the liberty is the prerequisite for living together in a political organization. As well as the political participation, the liberty rises from the human need to near the world and to feel himself like in an “agora”. The liberty, as well as the political participation, means action, but also the presence of the other one consciousness, the individual and /or groups desire not to become the instrument of somebody else without their will.